Analisis Strategi Pemasaran Pembiayaan KPR FLPP Pada Perumahan Bersubsidi Dengan Akad Murabahah (Studi Kasus PT Bank Syariah Indonesia,Tbk Syariah KC Medan Aksara) - Yuditia, Oppi Yolanda; Anggraini, Tuti; Harahap, Rahmat Daim (Journal of Student Development Informatics Management (JoSDIM), 2023)
The aim of this research is to analyze and find out the marketing strategy and financing procedures for FLPP KPR in subsidized housing at PT Bank Syariah Indonesia, Tbk KC Medan Aksara. The method used is qualitative with primary and secondary data sources. The results of this research are PT Bank Syariah Indonesia, Tbk KC Medan Aksara to develop and market FLPP KPR Financing products using the Marketing Mix method. 7P, namely Product, Price, Place, Promotion, People, Physical Evidence, Process strategy. Obstacles due to rising housing production costs (building materials, labor wages, and land prices which continue to soar). PT Bank Syariah Indonesia, Tbk KC Medan Aksara mostly uses murabahah financing contracts from the Financing Application stage, Financing Evaluation, Financing Structure, Issuance of Financing Decree, Contract Implementation, up to Financing Disbursement is in accordance with the provisions of the Fatwa of the National Sharia Council of the Indonesian Ulema Council No: 04/DSNMUI/IV/2000 concerning Murabahah. The obstacles found were seen from various parties, including debtors, developers and banks.